2009
DOI: 10.3109/14756360903179435
|View full text |Cite
|
Sign up to set email alerts
|

3-Arylidene-5-(4-isobutylphenyl)-2(3H)-furanones: a new series of anti-inflammatory and analgesic compounds having antimicrobial activity

Abstract: An ideal anti-inflammatory drug should have the desired effect in minimum dose with minimum side effects. Antimicrobial actions associated with such agents will be an added advantage as they broaden the spectrum of the compounds. Promising anti-inflammatory and antimicrobial activity together with low ulcerogenic properties of some 2(3H)-furanones, synthesized in our previous study, prompted us to investigate the effect of the isobutyl group on their pharmacological profile. Since compounds 3, 9, 13, and 14 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The presence of 2,5‐dihydro‐5‐methoxy‐2‐furanone compound in the crude extract of VITGAP173 either alone or in combination with the other compounds may be responsible for the activity. Furanones are known to possess broad spectrum biological activities including anti‐inflammatory and anticancer properties . The polyketides, actinofuranones A and B produced by marine‐derived Streptomyces strain CNQ766, isolated from Guam, was reported to exhibit activity against mouse splenocyte T cells and macrophages .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 2,5‐dihydro‐5‐methoxy‐2‐furanone compound in the crude extract of VITGAP173 either alone or in combination with the other compounds may be responsible for the activity. Furanones are known to possess broad spectrum biological activities including anti‐inflammatory and anticancer properties . The polyketides, actinofuranones A and B produced by marine‐derived Streptomyces strain CNQ766, isolated from Guam, was reported to exhibit activity against mouse splenocyte T cells and macrophages .…”
Section: Resultsmentioning
confidence: 99%
“…Furanones are known to possess broad spectrum biological activities including anti-inflammatory and anticancer properties. 56,57 The polyketides, actinofuranones A and B produced by marine-derived Streptomyces strain CNQ766, isolated from Guam, was reported to exhibit activity against mouse splenocyte T cells and macrophages. 58 The compounds N- [3-[6-hydroxyhexyl] aminopropyl] aziridine and N- [3hexylaminopropyl] aziridine may contribute to the biological activity assessed in the crude extract of VITGAP173.…”
Section: Gc-ms Analysis Of Vitgap173 Ea Extractmentioning
confidence: 99%
“…2004;Morten Hentzeret al 2002). The antibacterial potential of furanone has been studied and reported against nosocomial infections (Woo,Sang, Sung et al 2007), against Staphylococcus epidermidis which is one of the most common bacterial isolates from medical devices infections due to biofilm formation (Baveja et al 2004), and also seen to possess anti-inflammatory and analgesic property ( Alam et al 2010). Though there are no direct reports of studies correlating furfural and antimicrobial activity, characterization of some antimicrobial substances from seed coat of Tamarindus indica Linn.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…There have been reports showing compounds like furanone to be one of the causes of the antimicrobial effects concluding that these aroma compounds may contribute to the same, like 1H furanone and 3H furanone were evident in showing bacteriostatic activity in different media in the work done by Babynin et al [7]. Alam et al [8] demonstrated that the development of some synthesized furanone derivatives as promising antimicrobial as well as anti-inflammatory agents. Furanone is also shown to have role in biofilm inhibition and biofilm resistance in Salmonella enteric [9].…”
Section: Introductionmentioning
confidence: 96%